Determinants of preterm delivery among mothers who gave birth in hospitals of Wolaita zone, southern Ethiopia, 2023: unmatched case-control study - Cherinet Tilahun; Asmare Getie; Hiwot Tadesse; Temesgen Geta; Adisu Ashiko (BMC, 2024)
Abstract Background Preterm delivery refers to childbirth that occurs before 37 full weeks' gestation. Globally, around 13.4 million babies are born preterm annually, a million died due to its complications. Identifying its determinants is mandatory to decrease preterm birth and thereby neonatal deaths. Therefore, this study aimed to identify the determinants of preterm delivery among mothers who gave birth in hospitals in the Wolaita zone, southern Ethiopia. Methods A hospital-based unmatched case-control study design was conducted from March 29 to May 20, 2023, in the Wolaita zone, southern Ethiopia. Cases were women who gave birth after 28 weeks and before 37 completed weeks, and controls were women who gave birth at and after 37 and before 42 weeks of gestation from the first day of the last normal menstrual period. A consecutive sampling method was used. Data were collected by a structured interviewer-administered questionnaire. Data were coded and entered into Epi data 3.1 and analyzed by using SPSS version 25. Variables that had a P-value < 0.25 in the bivariate logistic regression analysis were entered into a multivariable logistic regression model. Finally, p-value < 0.05 was used to claim statistical significance. Result From a total of 405 eligible participants, 399 respondents (133 cases and 266 controls) participated in this study with a response rate of 98.52%. The result of the multivariable analysis shows that mothers who resided in rural areas [AOR = 2.78:95% CI (1.51-5.12)], not receiving support from their partner [AOR = 2.37:95% CI (1.24-4.51)], less than four antenatal care visits [AOR = 4.52:95%CI (2.38-8.57)], developed pregnancy-induced hypertension [AOR = 5.25:95%CI (2.27-12.14)] and exposed for intimate partner violence [AOR = 2.95:95%CI (1.105-7.85)], had statistically significant association with experiencing preterm delivery. Conclusion and recommendation Most of the determinants for preterm delivery have been proven modifiable. Thus, designing new strategies, providing comprehensive mobile clinic services to address hard-to-reach areas and Health care providers should give due attention to mothers with pregnancy-induced hypertension and exposure to intimate partner violence and increase the awareness of antenatal care follow-up and benefit of support during pregnancy to reduce preterm delivery.